La forme d’une ville : Watermark de Joseph Brodsky - René Alladaye (Anglophonia)
This short study of Joseph Brodsky’s Watermark (1992) discusses the poet’s visions of Venice and how they translate into writing. Three notions play a crucial part in this writing process: fusion, sensation and abstraction. The ultimate aim of this paper is to show how, for Brodsky, writing about Venice—or, more aptly put maybe—writing Venice, always revolves around the subtle combination of these three conceptual landmarks.